The Role Of The Semarang Police In Overcoming Narcotics Crime - Syafutra, Denni; Tohari, Mohamad (CV. Publikasi Indonesia, 2023)
Conceptually, crime prevention can be carried out either by using criminal justice (justice) or other means outside of criminal justice (non-judicial). Criminal law policies in dealing with narcotics in Indonesia have been carried out for a long time. Beginning with the enactment of the Drugs Ordinance (Verdoovende Middelen Ordonnantie, Stbl.1927No.278 jo. No.536). The Ordinance was later replaced by Law no. 9 of 1976 concerning Narcotics. Subsequently, the law was changed to Law no. 22 of 1997 concerning Narcotics until the emergence of Law no. 35 of 2009 as the latest update of the law on Narcotics. The main focus of the Semarang Police in tackling narcotics crimes lies in preventive efforts covering all efforts to prevent the abuse of narcotics or similar substances among the general public. Then narrow the space for movement and reduce the influence on other aspects of life.